Advanced techniques and nanotechnologies for point-of-care testing - Secchi, Valeria; Armanni, Alice; Barbieri, Linda; Bruno, Antonia; Colombo, Alessandro; Fumagalli, Sara; Kukushkina, Ekaterina A.; Lorenzi, Roberto; Marchesi, Letizia; Moukham, Hind; Paleari, Alberto; Ronchi, Alessandra; et al. (Frontiers in Nanotechnology, 2025)
Hospitals and other healthcare facilities harbor a complex interplay of microbial pathogens. The correct understanding of pathogens distribution and evolution is therefore crucial for infections control and for the design of effective prevention strategies. In parallel, the integration of cutting-edge nanotechnologies for the early detection and monitoring of these specific target pathogens is considered the most effective approach to face nosocomial infections. In this context, point-of-care (POC) testing, also known as near-patient testing, is becoming increasingly important. In this review we provide a systematic insight into the recent scientific and technological advances in pathogen detection that explore advanced nanotechnologies to realize devices and nanobiosensors, with improved selectivity and sensitivity. In particular, we report on the most diffused and affordable nanotechnologies developed and still developing for POC testing, with the aim to increase the sensitivity, speed and accuracy of pathogens detection in different environments, from intensive care units to outside the laboratory and hospital settings. The text is sub-divided in several sections, each one focused on different type of nanomaterials and techniques actually employed.